2016
DOI: 10.1097/md.0000000000003239
|View full text |Cite
|
Sign up to set email alerts
|

Can Dynamic Contrast-Enhanced MRI (DCE-MRI) and Diffusion-Weighted MRI (DW-MRI) Evaluate Inflammation Disease

Abstract: The aim of the study was to investigate diagnosis efficacy of dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted MRI (DW-MRI) in Crohn's disease (CD). To find out the correlations between functional MRI parameters including Ktrans, Kep, Ve, Vp, and apparent diffusion coefficient (ADC) with a serologic biomarker. The relationships between pharmacokinetic parameters and ADC were also studied.Thirty-two patients with CD (22 men, 10 women; mean age: 30.5 years) and 18 healthy volunteers without any inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…[ 15 ] Meanwhile, studies have employed this technique to assess neovascularization in inflammatory diseases. [ 16 , 17 ] We have assessed the role of DCE-MRI in diagnosis and assessment for CD, [ 18 ] such findings are similar to other researches. [ 19 21 ] In this paper, we present a preliminary study of CD by DCE-MRI and hypothesize that the parameters of DCE-MRI can be used to evaluate the therapeutic response.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…[ 15 ] Meanwhile, studies have employed this technique to assess neovascularization in inflammatory diseases. [ 16 , 17 ] We have assessed the role of DCE-MRI in diagnosis and assessment for CD, [ 18 ] such findings are similar to other researches. [ 19 21 ] In this paper, we present a preliminary study of CD by DCE-MRI and hypothesize that the parameters of DCE-MRI can be used to evaluate the therapeutic response.…”
Section: Introductionsupporting
confidence: 71%
“…In this study, K trans and BV decreased significantly after treatment and good correlation was shown between Δ K trans , ΔBV, and changes of clinical indicators. In our prior study, [ 18 ] we have found the parameters of DCE-MRI including K trans had significant correlation with CRP. Sinha et al [ 37 ] concluded that the contrast agent rapidly passed from the vascular space into the EES, resulting in mural enhancement in CD patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Conventional Magnetic Resonance Index of Activity (MaRIA) is calculated by multiple embedded formulas by wall thickness, relative contrast enhancement (RCE) and two qualitative variables, edema and ulceration, to identify inactive and active disease[ 10 ]. Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) has been widely accepted as a tool to monitor disease progression in other organs[ 11 - 13 ] and can provide quantitative perfusion and permeability information on the bowel wall to accurately localize lesions, monitor disease activity and evaluate treatment responses[ 14 - 17 ]. Menys et al [ 18 ] proposed grading CD with MRE on the basis of magnetic resonance (MR) contrast enhancement, indicating that DCE-MRI may be useful in grading CD.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with morphological imaging, quantitative dynamic contrast enhanced magnetic resonance imaging(DCE-MRI),basing on a pharmacokinetic model, have been successfully used to assess changes in different diseases [3,[15][16] .It can provide su cient information on microenvironment changes and could be used to assess the severity of in ammation quantitatively [17] .In the management of early AS joint, there is also a need for reliable noninvasive quantitative monitoring biomarker to closely assess status of in ammatory progression. In 2019, the ASAS-MRI work group have pointed out that increased signal on contrast-enhanced images of the joint space of the cartilaginous portion of the SIJ re ected in ammation at the osteochondral interface, as this would be consistent with the understanding of early histopathological feature of AS [18] .Cognizant to this, studies geared on improving techniques for quantitative evaluation of micro-environment permeability of the joint space before edema and in ammation visualized in adjacent bone marrow of SIJ are necessary.…”
Section: Introductionmentioning
confidence: 99%